2017
DOI: 10.1093/qje/qjx049
|View full text |Cite
|
Sign up to set email alerts
|

Interfirm Relationships and Business Performance*

Abstract: We organized business associations for the owner-managers of randomly selected young Chinese firms to study the effect of business networks on firm performance. We randomized 2,800 firms into small groups whose managers held monthly meetings for one year, and into a "no-meetings" control group. We find that: (1) The meetings increased firm revenue by 8.1 percent, and also significantly increased profit, factors, inputs, the number of partners, borrowing, and a management score; (2) These effects persisted one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
112
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(134 citation statements)
references
References 65 publications
(42 reference statements)
8
112
2
Order By: Relevance
“…One way to boost women's self-confidence and expand their business networks at the same time could be through entrepreneur support groups. A recent study of young firms in China found that firms randomly assigned to attend peer support meetings significantly increased sales, profits, employment, productivity, and the number of business partners (Cai and Szeidl, 2016). However, this study did not address whether the impacts of peer support groups were different by gender, which is an important area of future research.…”
Section: 2mentioning
confidence: 86%
“…One way to boost women's self-confidence and expand their business networks at the same time could be through entrepreneur support groups. A recent study of young firms in China found that firms randomly assigned to attend peer support meetings significantly increased sales, profits, employment, productivity, and the number of business partners (Cai and Szeidl, 2016). However, this study did not address whether the impacts of peer support groups were different by gender, which is an important area of future research.…”
Section: 2mentioning
confidence: 86%
“…where y it is the dependent variable measuring the firms' performance in terms of total turnover growth for firm i at time t (Cai & Szeidl, 2018); treat i is a dummy variable taking value 1 if the firm signed a network contract in 2013 and 0 otherwise; time t is a dummy variable taking value 1 from the year of the treatment effect (2013) and 0 before; treat * time it is the interaction term between the treated and time variables, which is the main focal regressor in the DID model. ID it defines ID membership at the firm level, to control for firms' belonging to a district, as another networking alternative.…”
Section: Methodsmentioning
confidence: 99%
“…These benefits might not be as large for microenterprises, however. Small firms do not benefit, at least not as much, from formal and informal meetings between owners (Cai and Szeidl, 2018;Fafchamps and Quinn, 2018). Microenterprises also do not seem to interact with each other enough for there to be spillover effects on other firms when one firm receives an inspection visit to verify that it is registered (de Andrade et al, 2013).…”
Section: Inter-firm Relationshipsmentioning
confidence: 99%